(untitled) (Zoo Botanica, 2025)
Cotton productivity is threatened by climate change driven heat extremes, unpredictable rainfall, Cotton Leaf Curl Disease (CLCuD) and insect pests. The limited availability of climate resilient cotton cultivars is a primary concern among farmers in Pakistan. To address this bottlenecks, a new climate smart, high yielding, early maturing Bt. cotton variety “FH-492” tolerant to Cotton Leaf Curl Disease (CLCuD) developed at the Cotton Research Station, AARI, Faisalabad through hybridization of FH-113 (Bt, bollworm resistant) and FH-1200 (Non-Bt., heat tolerant). The F₂ to F₆ generations were advanced through pedigree selection (2011–2016) and subsequently evaluated in Preliminary Yield Trials (PYT), Advanced Yield Trials (AYT), Provincial Coordinated Cotton Trials (PCCT), and multi-location National Coordinated Varietal Trials (NCVT) from 2017 to 2021. FH-492 proved superior performance and produced 19.2% and 15.1% higher seed cotton yield than the check variety CIM-602 during 2019–20 and 2020–21, respectively, in the National Coordinated Varietal Trial (NCVT). Fiber quality assessed by standardized High Volume Instrument (HVI) demonstrated industry compatible and thermally stable fiber profiles with mean values of a staple length (29.80 mm), ginning out-turn (42%), micronaire (4.5 µginch⁻¹), fiber strength (31 gtex⁻¹) and a uniformity index (88%). Punjab Seed Council (PSC) finally approved the variety for general cultivation in 2021. Morphologically, FH-492 Plants are medium compact (160–180 cm), cluster boll habit, 50–70 bolls per plant, maturing in 150–160 days with a seed cotton yield potential of 5500 kg/acre. Thus, FH-492 offers a sustainable solution for cotton production under changing climatic conditions and meets the needs of farmers and the cotton industry.